Efectos jurídicos de las resoluciones en los procesos de Tenencia Compartida - KatLata Llamuca, katherin Daniela (2020)
According to the provisions of article 69, numeral 1 of the Constitution of the Republic of Ecuador, the State must promote responsible maternity and paternity. It means the equal exercise of the rights and obligations of the father and mother about their children, especially related to parenting, education, integral development, especially when parents are separated for any reason. The Childhood and Adolescence Code, in its article 100, establishes parental responsibility. It creates equal obligations to the father and mother about the protection of the rights of their common children, such as the right to coexistence family member who understands the child's right to maintain emotional relationships with their parents on equal terms. Based on the already mentioned factor, this research develops an analysis of the issued resolutions in the shared tenure processes that is carried out. Although it is not being developed in the Code of Children and Adolescence, it has been applied by judges of the Judicial Units of Women, Family, Children and Adolescents. Therefore, it has been convenient to observe the right of children to live with both of their parents. For this reason, this reason, this research shows the positive effects of sentences on children and adolescents. An analysis of several sentences of shared tenure out using the inductive- deductive method, as well as the synthetic, analytical approach was used, which allowed to get relevant information on the proposed topic. Moreover, it was performed a field investigation where some experts shared opinions about this problem.